Risk Factors Of Malaria At Tanjung Ria Health Center, Jayapura City, Indonesia - Sejati, Anjar Ariansyah; Medyati, Novita; Sandjaja, Bernard (Sean Institute, 2024)
Malaria is caused by parasites of the genus plasmodium and transmitted by Anopheles mosquitoes.Sp is one of the most prevalent diseases in Jayapura City. This study aims to determine the risk factors for malaria incidence in the working area of Tanjung Ria Health Center, Jayapura City in 2023. This type of research is analytic quantitative research with a cross sectional approach. The sampling technique used systematic sampling technique with a total sample of 72 respondents. The data collected were then analyzed with univariate, bivariate and Chi Square statistical tests. The results of this study showed that the variables that became the dominant risk factor were Gender (p-value 0.033, PR = 1.867 CI 95%( 1.045-3.334), Use of Mosquito Net/ITN (p-value 0.042, PR = 1.67, CI 95% (1.091-2.575), Distance from House to Mosquito Breeding (p-value = 0.084, PR = 1.681, CI 95% (1.119-2.526). The results of this test prove that gender and distance to mosquito breeding sites have an association with malaria incidence at Tanjung Ria Health Center, Jayapura City.